Fondaparinux vs warfarin for the treatment of unsuspected pulmonary embolism in cancer patients - Abdel-Razeq H; Mansour A (Dove Medical Press, 2016)
Hikmat Abdel-Razeq,1 Asem Mansour2 1Department of Internal Medicine, 2Department of Radiology, King Hussein Cancer Center, Amman, JordanWe read with great interest the study published on June 23, 2016 by Amato et al entitled “Fondaparinux vs warfarin for the treatment of unsuspected pulmonary embolism in cancer patients.”1 While we value the importance of this study in highlighting this important topic, we have several issues to be addressed.View original paper by Amato and colleagues.